2023
DOI: 10.15294/kemas.v18i3.39909
|View full text |Cite
|
Sign up to set email alerts
|

Complaints of Low Back Pain in Tailors

Santy Deasy Siregar,
Putranto Manalu,
Rapael Ginting
et al.

Abstract: Low back pain (LBP) is one of the musculoskeletal disorders as a result of incorrect ergonomics. The impact caused by low back pain is bad posture, stiffness, pinched nerve, and muscle weakness. This study aims to determine the relationship between ages, years of service, length of sitting, work posture, and the chair’s ergonomics with complaints of low back pain in tailors at Pasar Petisah, Kota Medan, with 35 workers based on inclusion and exclusion criteria. The research tools are interviews, observations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
3
1
0
Order By: Relevance
“…These results are in line with research conducted by Siregar et al (2021) who said that the results of the chi-square statistical test obtained a p value of α (0.023 < 0.05), thus it can be seen that Ha is accepted, meaning that there is a relationship between working hours and complaints of skin disorders among fish traders. (Siregar et al, 2021) Research conducted by Ahmad et al (2020) shows that exposure time has a relationship with complaints of skin disorders among fish traders with a significance value of (0.000). (Ahmad et al, 2020) Each worker has a different exposure time.…”
Section: Relationship Between Exposure Time and The Incidence Of Cont...supporting
confidence: 90%
See 2 more Smart Citations
“…These results are in line with research conducted by Siregar et al (2021) who said that the results of the chi-square statistical test obtained a p value of α (0.023 < 0.05), thus it can be seen that Ha is accepted, meaning that there is a relationship between working hours and complaints of skin disorders among fish traders. (Siregar et al, 2021) Research conducted by Ahmad et al (2020) shows that exposure time has a relationship with complaints of skin disorders among fish traders with a significance value of (0.000). (Ahmad et al, 2020) Each worker has a different exposure time.…”
Section: Relationship Between Exposure Time and The Incidence Of Cont...supporting
confidence: 90%
“…These results are in line with research conducted by Anggraini and Utami (2022), which showed that the Fisher's exact test p-value = 0.020 was smaller than 0.05, which means that there is a relationship between the use of PPE and the incidence of dermatitis. (Anggraini & Utami, 2022) In line with research conducted by Siregar et al (2021) where the results of data analysis obtained a chi-square of 10.417 with a probability of 0.001 < 0.05, which means that there is a significant relationship between the use of personal protective equipment and the incidence of dermatitis at fish sales places. (Siregar et al, 2021) Observation results at the research location show that many fish traders still underestimate the use of PPE.…”
Section: Relationship Between Ppe Use and The Incidence Of Contact De...supporting
confidence: 74%
See 1 more Smart Citation
“…Silviana et al utilized anthropometric measurements as a design tool for ergonomic furniture to reduce the likelihood of various health problems and improve employee performance [1]. Siregar et al conducted research suggesting that non-ergonomic postural habits can lead to lower back pain and that adding back support to chairs is beneficial in reducing this pain [2]. Lu et al analyzed the pressure distribution in forward-leaning and upright sitting postures [3], and Moon et al optimized the elastic support material on the chair's surface to improve comfort [4].…”
Section: Introductionmentioning
confidence: 99%